2005
DOI: 10.1177/09680519050110060401
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the requirement for CD40—CD154 interactions in resistance to infections with attenuated Salmonella

Abstract: Salmonella species include facultative intracellular pathogens which reside preferentially within cells of the host's reticulo-endothelial system. Resistance to Salmonella involves a collaboration between cells of the innate and adaptive immune systems, and protective immunity requires cell-mediated and humoral-immune responses. CD40-CD154 interactions are of central importance in the induction of cellular immune responses. In the present study, CD154-deficient (CD154(-/-)) mice were used to assess the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For protection experiments, reduction in bacterial replication was used as a measure of protective immunity, and MV-immune mice were infected via the i.p. route with ϳ1 ϫ 10 5 CFU SL3261, which allows the survival of infected animals (55)(56)(57)(58)(59)(60)(61). After MV immunization and live bacterial challenge (see above), bacterial burden in infected tissues was used as a measure of protective immunity.…”
Section: Mice Immunizations and Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For protection experiments, reduction in bacterial replication was used as a measure of protective immunity, and MV-immune mice were infected via the i.p. route with ϳ1 ϫ 10 5 CFU SL3261, which allows the survival of infected animals (55)(56)(57)(58)(59)(60)(61). After MV immunization and live bacterial challenge (see above), bacterial burden in infected tissues was used as a measure of protective immunity.…”
Section: Mice Immunizations and Infectionsmentioning
confidence: 99%
“…6), indicating that MV-induced B and T cells respond to infection with live bacteria. Because it is firmly established that protectively immunized mice inhibit bacterial replication during live Salmonella challenge (41), we determined organ CFU as a measure of protective immunity in MV-immune mice infected with viable Salmonella SL3261, which allows the survival of infected animals (55)(56)(57)(58)(59)(60)(61). In contrast to sham-immunized controls, MV-immune mice had decreased bacterial CFU in all organs measured after infection with live Salmonella (Fig.…”
Section: Mvs Prime Salmonella-specific Immunity In Vivo That Significmentioning
confidence: 99%
“…Protection against S. typhimurium requires Th1-type immune responses. [22][23][24]43 Moreover, a robust antibody response is known to be required for resistance against virulent Salmonella infection. 22,44,45 Our results demonstrated that, contrary to expectations, paraoxon treatment rendered the animals more resistant to Salmonella infections.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if paraoxon exposure had any effect on susceptibility to infection, mice were treated with paraoxon for 3 weeks and then inoculated with a lethal dose of the facultative enteric pathogen S. typhimurium . Protection against S. typhimurium requires Th1‐type immune responses 22–24,43 . Moreover, a robust antibody response is known to be required for resistance against virulent Salmonella infection 22,44,45 .…”
Section: Discussionmentioning
confidence: 99%